Things Little Girls Have No Business to Know Anything about: The Crimes of Aurora Floyd - Ward, Ian (Columbia Journal of Gender and Law, 2011)
The case of Aurora Floyd horrified mid-Victorian England. It is true that her fate evinced sympathy too, but the horror was the greater. We would not be so horrified today, though the offence she committed remains proscribed in English criminal law. Aurora Floyd was a bigamist; her crime, and even more so her sin, was to have two husbands living concurrently. And newspaper editors knew then, as they know today, that the English-reading public likes nothing better than to speculate on a spot of sex and crime over the breakfast table. Aurora was pretty too, and had married fortunately, or at least she had the second time. Her husband was a stolid member of the landed Yorkshire aristocracy. The story of Aurora Floyd came to the attention of mid-Victorian middle England over the winter of 1862, as the nation struggled to come to terms with the murderous bigamy of Lucy Audley, discovered the year before. Aurora and Lucy had something else in common too, aside from their shared criminality. They were fictive, the eponymous heroines of the two “sensation” novels with which Mary Elizabeth Braddon had taken literary England by storm in the first years of the 1860s. The fact that Aurora and Lucy were fictional did not, of course, lessen the threat that many perceived in their creation. On the contrary, it made their crimes all the greater. The case of Lucy Audley has long attracted critical commentary; Lady Audley’s Secret is still recognised as the one of the canons of mid-Victorian fiction, more particularly still mid-Victorian “sensation” fiction. Literary history has not been so kind to Aurora Floyd, which has in comparison, largely evaded critical attention during the last century and a half.I The purpose of this article is to revisit Aurora Floyd, and more particularly the crimes of its protagonist, as an exercise in legal and literary history.